THE SYMBOLIC MEANING OF THE DRAGON BOAT AS A TRADITION IN SOCIOLOGICAL ANTROPOLOGICAL STUDY FOR THE BERAU TRIBE, EAST KALIMANTAN - Hayati, Nurul; Bahzar, Moh; Wingkolatin, Wingkolatin (Unmul Civic Education Journal, 2022)
The purpose of this study was to determine the sociological anthropological review of the symbolic meaning of the dragon boat as a custom for the Berau tribe in Gunung Tabur Village, Gunung Tabur District, Berau Regency. This type of research is descriptive qualitative. The focus of this research is to find out the community's view of the customs carried out in Berau Regency in the midst of the progress of the times and the form of preservation of customs through a sociological anthropological review. To define the customs of the Berau tribal dragon boat in the process of carrying out a sociological anthropological review and the results of an anthropological sociological review. Data collection techniques used are observation, interviews and documentation. The data analysis technique used is data reduction, data display, data presentation and drawing conclusions. The results of this study indicate that the Dragon Boat Custom which is held in Berau Regency is known as the Baturunan Parahu which means lowering the parahu, this custom is carried out on the anniversary of Berau Regency and if a boat is lowered then a boat race begins, before the boat is lowered there are several requirements which must be completed such as preparing some spices, namely betel leaf, areca nut, lime, nutmeg, yellow rice, candles, and on the side of the boat on display with areca nut in front and behind it. Some of these requirements were brought by the traditional leaders and residents of Gunung Tabur when the boat was lowered. Previously, a caterpillar dance was also held to welcome the start of the dragon's parachute being lowered